2017
DOI: 10.1007/s00216-017-0514-4
|View full text |Cite
|
Sign up to set email alerts
|

An LC-MS chemical derivatization method for the measurement of five different one-carbon states of cellular tetrahydrofolate

Abstract: The cofactor tetrahydrofolate (THF) is used to reduce, oxidize and transfer one-carbon (1C) units required for the synthesis of nucleotides, glycine, and methionine. Measurement of intracellular THF species is complicated by their chemical instability, signal dilution caused by variable polyglutamation and the potential for interconversion among these species. Here we describe a method using negative mode liquid chromatography-mass spectrometry (LC-MS) to measure intracellular folate species from mammalian cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…however, we were able to detect four more analogs of FA. 33 The new APCI-MS approach was less sensitive when compared with the ESI-MS/MS, but the LOQs for most of the intermediates were comparable to the work of Chen et al 43 Nevertheless using the APCI-based method, we retrieved the concentration of DHF, which was not possible using the ESI ion source. We speculate that APCI analyses can be less susceptible to matrix effects (including ion suppression) when compared with ESI, which may explain the better ionization of DHF.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…however, we were able to detect four more analogs of FA. 33 The new APCI-MS approach was less sensitive when compared with the ESI-MS/MS, but the LOQs for most of the intermediates were comparable to the work of Chen et al 43 Nevertheless using the APCI-based method, we retrieved the concentration of DHF, which was not possible using the ESI ion source. We speculate that APCI analyses can be less susceptible to matrix effects (including ion suppression) when compared with ESI, which may explain the better ionization of DHF.…”
Section: Discussionmentioning
confidence: 74%
“…The quantification of the folate pool in biological samples remains a challenge due to the complexity of the sample matrix. Work of Chen et al required a solid phase extraction (SPE) step using cyclohexy‐based chemistry cartridges for the enrichment of FA derivatives in cultured human cells . A study from Pawlosky et al used C18 Sep‐Pak cartridges, whereas Nandania et al used strong anion exchange cartridges for the enrichment in human whole blood .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we sought to examine the effects of MTR knockout on folate species required for nucleotide synthesis. The folate precursor for purine synthesis, 10-formyl THF, is indistinguishable from a closely related species 5,10-methenyl THF by LC/MS due to known interconversion after cell lysis 32,33 . We observed that MTR knockout results in depletion of the combined levels of 5,10-methenyl THF and 10-formyl THF ( Figure 2D-E), suggesting that purine synthesis could be affected.…”
Section: Resultsmentioning
confidence: 99%
“…The methodology employed in a previous study (46) was most successful when cell densities were high and compounds that blocked folate metabolism were used to increase the concentration of the analytes. This technique has recently been supplanted by an approach that uses derivatization agents to trap unstable methylene-THF intermediates as stable methyl-THF intermediates (47). As the derivatization step may lead to dechlorination, this method was not used in the present study.…”
Section: Discussionmentioning
confidence: 99%